Effect of grazing intensity on rangeland productivity in Northern Libyan area of Syrt - Pardini A.; Battaglia M.; Mugnai E. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Urbanization and irrigation plans that took place in Libya during the last decades have started also to concentrate livestock rearing, consequently for the first time it would now be possible to restrict overgrazing in some areas of the rangeland. Rangeland rehabilitation after long overgrazing by wild animals and nomadic herds should take a start from a preliminary investigation of the present productivity and the effects of grazing limitations. A trial has been done in 2009 in the Syrt rangeland few months before the start of the war, in order to compare forage productivity of the grazed rangeland with that of areas where grazing was avoided. The trial was managed thanks to agreements of the Italian Agronomic Institute for Overseas (Ministry of Foreign Affairs), University of Florence, and University of Syrt now destroyed. The results have shown a very little productivity of the native vegetation, but also the possibility to rise it considerably if grazing can be suspended for a period of time. Further investigation would be needed soon as the area will be secured again for national and international operators. However our results show also that the little productivity of the rangeland cannot be enough to give better lives to rural people and suggest that herding and rangeland uses should be linked to other sectors of the national economy and integrated in a modern scenario.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)